2007
DOI: 10.1093/eurheartj/ehm114
|View full text |Cite
|
Sign up to set email alerts
|

Late incomplete apposition after drug-eluting stent implantation: incidence and potential for adverse clinical outcomes

Abstract: Late-acquired ISA was observed in 5.1% of patients after DES implantation and is related to regional vessel positive remodelling. The relationship between late-acquired ISA and long-term adverse outcomes (e.g. stent thrombosis) requires further analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 21 publications
4
48
0
12
Order By: Relevance
“…These results were consistent with our previous report. 3 Although intravascular ultrasound finding of ISA is known as one of the risk factors for stent thrombosis, [5][6][7][8][9] OCT finding of ISA remains unclear whether it can be a risk factor for stent thrombosis or not. In this study, the maximal ISA area and distance were greater in lesions with PSS than in lesions without PSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with our previous report. 3 Although intravascular ultrasound finding of ISA is known as one of the risk factors for stent thrombosis, [5][6][7][8][9] OCT finding of ISA remains unclear whether it can be a risk factor for stent thrombosis or not. In this study, the maximal ISA area and distance were greater in lesions with PSS than in lesions without PSS.…”
Section: Discussionmentioning
confidence: 99%
“…October 2012 relation to very late stent thrombosis (VLST) after drug-eluting stent implantation, [5][6][7][8][9] and results of many studies in which ISA was assessed by optical coherence tomography (OCT) have been published in recent years. 10,11 An ulcer-like appearance around the SES struts observed by OCT has been reported recently.…”
Section: Circ Cardiovasc Intervmentioning
confidence: 99%
“…Hoffmann et al 19 described a higher incidence of myocardial infarction in patients with ISA after 4 years of follow-up compared with patients without ISA. Siqueira et al 10 performed follow-up on patients for a mean of 29 months and observed an increased incidence of stent thrombosis in patients with ISA. Cook et al 20 reported similar results, finding that patients presenting with stent thrombosis after a minimum of 12 months following stent deployment had a higher incidence of ISA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the architecture of stents within coronary vessels and have noted the presence of ISA to the vessel wall. [8][9][10] Because this finding may be associated with adverse clinical events such as late stent thrombosis 10,11 in the coronary circulation, we sought to identify the presence of any ISA within the intracranial circulation in patients undergoing stent-mediated coiling by using the self-expanding intracranial EN (Cordis, Miami Lakes, Florida). Correlating our findings with angiographic FPCT, we describe here a new crescent-shaped flow signal intensity external to the stent struts on 3T-MRA as a marker for ISA in EN-treated aneurysms and describe the morphologic characteristics of target vessels that predispose to poor stentϪvessel wall apposition.…”
mentioning
confidence: 99%
“…Resposta de hipersensibilidade/reação inflamatória induzida pelas altas concentrações do fármaco nas hastes do stent ou pela presença do polímero sintético pode levar a remodelamento vascular positivo, crescimento desproporcional da área da membrana elástica externa do vaso em relação à área da placa aterosclerótica/camada média [4][5][6] . Tal fenômeno pode levar à aposição incompleta tardia das hastes do stent, atuando como fator de risco para trombose tardia desses dispositivos 7,8 .…”
unclassified